Link between dynamic capability and sustainable entrepreneurship: The mediation role of digital networking - Nur, Sofyan Ashari; Muafi, Muafi (Jurnal Siasat Bisnis, 2025)
Purpose – This study analyses the influence of three main parts of dynamic capability, namely integration capability, adaptive capability, and reconfiguration capability on sustainable entrepreneurship in online businesses in e-commerce. This study also analyses the effect of digital networking on sustainable entrepreneurship and the mediating role of digital networking on the influence of dynamic capability parts on sustainable entrepreneurship.Design/methodology/approach – The analysis in this study was conducted using quantitative methods. The population used is online business managers in e-commerce in Yogyakarta. The sample selection was carried out by stratified random sampling and collected 180 respondents. Research data was collected using a questionnaire with google form and obtained according to the target of 180 respondents, then the analysis was carried out using the structural equation model (SEM) method using Smart-PLS4. Findings – The results that the three main parts of dynamic capability-integration capability, adaptive capability, and reconfiguration capability-significantly affect sustainable entrepreneurship. Furthermore, it was found that digital networking has a positive effect on sustainable entrepreneurship and can mediate the effect of integration capability, adaptive capability, and reconfiguration capability on sustainable entrepreneurship.Research limitations/implications – This study may be limited to a particular industry or sector, which may limit the generalisability of the results to other industry contexts. Future research is recommended to explore this relationship in various industries with different features, such as manufacturing, services, or high-tech sectors.Practical implications – This research provides strategic guidance for companies looking to improve their entrepreneurial sustainability. Managers should focus on strengthening digital networking within their organisations to maximise the positive impact of integration, adaptive and reconfiguration capabilities.Originality/value – This research offers a strategic approach that combines the idea of dynamic capability with digital networking in sustainable entrepreneurship.